Sustainable Technology Assessment and Sustainable Scenarios of Techno Social Phenomena - Amemiya Ramírez, Michiko (Journal of Sociocybernetics, 2014)
Sustainable technology can be described as a technological subsystem with marginal or no negative impacts on other technological systems, as well as the environment, the society and the economy. To identify such technologies it is necessary to describe their behavior and their present and future interactions with those systems. Due to social dynamics, a complete assessment to identify sustainable technologies requires a hard systems analysis and a soft system analysis. A hard system analysis is useful to assess the interactions, behavior and characteristics of the technology quantitatively. A soft system analysis is convenient to describe other characteristics and interactions through qualitative and non measurable characteristics. System Dynamics is a useful resource to forecast the behavior of technology related systems for which the hard systems logic is the dominant paradigm. Key variables related to technological assessment subject to system dynamics modeling include population growth, efficiency, energy intensity, release of greenhouse effect gases, and the expansion of risk areas. The selection of indices and variables is determined according to the studied technology. Therefore, a detailed description of the technology is fundamental. In this paper, sustainable technology is briefly described, an example of systems dynamics to forecast quantitative qualities of socio-technological system and conclusions are presented.